Application of Electron Backscatter Diffraction to evaluate the ASR risk of concrete aggregates. (May 2017) - Rößler, C.; Möser, B.; Giebson, C.; Ludwig, H.-M.
Abstract: Alkali-Silica Reaction (ASR) is a frequent cause of reduced concrete durability. Eliminating the application of alkali reactive aggregates would reduce the quantity of ASR concrete deterioration in the field. This study introduces an Electron Backscatter Diffraction (EBSD) technique to distinguish the ASR risk of slow-late reacting aggregates by measuring microstructural properties of quartz. Quantifying the amount of quartz grain boundaries and the associated misorientation of grains can thereby be used to differentiate microstructures bearing an ASR risk. It is also shown that dissolution of quartz in high pH environments occurs along quartz grain and subgrain boundaries. Results of EBSD analysis are compared with ASR performance testing on concrete prisms and optical light microscopy characterization of quartz microstructure. EBSD opens new possibilities to quantitatively characterize microstructure of quartz in concrete aggregates with respect to ASR. This leads to a better understanding on the actual cause of ASR.